Pengaruh adukan dan kepekatan partikel silicon karbida sebagai penguat terhadap kelakuan salutan komposit matriks nikel - Badarulzaman, Nur Azam (2010)
Affordable quality housing is vital in developing countries to meet its growing population. Development of a new cost effective system is crucial to fulfill these demands. In view of this, a study is carried out to develope a Precast Lightweight Foamed Concrete Sandwich Panel (PLFP), as a new affordable building system. Experimental investigation and finite element analysis to study the structural behaviour of the PLFP panel under axial load is undertaken. The panel consists of two foamed concrete wythes and a polystyrene insulation layer in between the wythes. The wythes are reinforced with high tensile steel bars and tied up to each other through the polystyrene layer by steel shear connectors bent at an angle of 45º. The panels are loaded with axial load until failure. The ultimate load carrying capacity, load-lateral deflection profile, strain distributions, and the failure mode are recorded. Partial composite behaviour is observed in all specimens when the cracking load is achieved. Finite element analysis is also carried out to study the effect of slenderness ratio and shear connectors which are the major parameters that affect the strength and behaviour of the panels. An empirical equation to predict the maximum load carrying capacity of the panels is proposed. The PLFP system proposed in this research is able to achieve the intended strength for use in low rise building. Considering its lightweight and precast construction method, it is feasible to be developed further as a competitive IBS building system.